Spreading kinetics of oil droplets over three different substrates. Issue 17 (2nd September 2021) - Wang, Junchao; Cao, Yijun; Li, Guosheng; Zou, Yuchao; Hao, Xiaodong
ABSTRACT: Spreading of liquids over solid surfaces is an interesting and important phenomenon from both fundamental and applied viewpoints. This paper intensively studied the spreading kinetics of oil (oleic acid) droplets over three different substrates (SiO2, mica, and sapphire) from both short-time and long-time spreading process based on the dynamic contact angle, spreading diameter, and spreading area. Results showed that at the short-time spreading process, the contact angle continued to decrease with time for all studied substrates while both spreading diameter and spreading area exhibited an opposite trend. On the other hand, the contact angle, spreading diameter and spreading area reached the plateau during the long-time spreading process. And the relative order of the equilibrium contact angle was as followed: mica > sapphire > SiO2, while that of both maximum spreading diameter and maximum spreading area was as followed: sapphire > SiO2 > mica. These differences are mainly due to the different affinity of oleic acid on various substrates, which can reflect the effect of surface wettability on spreading kinetics. It is further found that surface wettability is influential throughout the entire spreading process, in other words, it not only affects the spreading behavior of drops but also changes the static contact angle.